KPI Assessment Using Business Process Analysis, Deterministic and Stochastic Monte Carlo Simulation. Case: KPI Fuel Ratio lt/bcm/km - Gilang Artha Putra; Nur Budi Mulyono (AIBPM Publisher, 2021)
The study investigates the basic behavior of Key Performance Indicator (KPI) Fuel Ratio (lt/bcm/km) which has created confusion among analysts and decision makers in a mining company by its anomaly in measuring fuel efficiency. This investigation is a part of a KPI Life Cycle which known as KPI Assessment phase to review if the KPI still has the capability to provide a good measurement. The method of this research is using combination of both qualitative and quantitative approach. Started with Business Process Analysis (BPA) approach to modelling current KPI formulation into a flow chart diagram with cause-effect technique. Then the results from BPA phase are validated through simulation analysis in both deterministic and stochastic Monte Carlo methods. To support the validation phase, actual operational data is collected from database. The results discovered that anomaly of this KPI was occurred because current formulation incorporating parameters that irrelevant with haul distance variable. Once the irrelevant parameters were eliminated from the calculation in the simulation experimentation, the anomaly of the KPI was disappeared. The findings of this research suggest that the KPI measurement required a new formulation to create a more reliable and robust tool to monitor the fuel efficiency.